Peran Serikat Pekerja dalam Mengoptimalkan Kualitas Hubungan Industrial Pada PT Sansan Saudatex Jaya - Resya Dwi Marselina; Siti Saripah; Siti Anggia Denisa; Putri Lathifah; Rangga Agus Sopian; Ganjar Nugraha (Global Leadership Organizational Research in Management, 2024)
Industrial relations problems are still high, even though they can be overcome by optimizing the role of trade unions in realizing quality industrial relations. The aim of the research is to describe and analyze the role of trade unions in optimizing the quality of industrial relations, the factors that encourage and hinder them, as well as efforts to overcome existing obstacles. HRD informants representing labor unions, management staff and government agencies, were obtained purposively. Data was obtained using interviews and documentation studies, then analyzed qualitatively. Research results: Labor Unions play an optimal role in realizing quality industrial relations; (2) The driving factor is involvement in company, strategic position, communication, and regulation. Inhibiting factors are the quality and quantity of human resources, low worker participation, no cadre formation program, internal conflict, company intimidation, and lack of supervision; and (3) Efforts to overcome inhibiting factors are cadre formation, socialization,solidarity, communication, and supervision